Poster: MR and IoT convergence platform with AI support for disaster recognition - Kil, Woogeun; Ko, Kwangpyo; Lee, Seungwoon; Roh, Byeong Hee (MobiSys 2019 - Proceedings of the 17th Annual International Conference on Mobile Systems, Applications, and Services, 2019)
Because disaster situations can cause damage to people and property, fast recognition and Countermeasure is important. IoT and MR, the technologies that have become popular nowadays, expected to play a key role in this domain. In this paper, we will introduce MR and IoT Convergence Platform with AI Support for Disaster Recognition This platform can recognize a disaster situation with sensors and AI system, and report to the user's MR devices. Also, we build a prototype using OneM2M-based Mobius Platform, Microsoft Hololens, and CNN-based AI Camera for proving feasibility.
Keywords: AI systems; Artifical intelligence; Disaster countermeasures; Disaster situations; Fast recognition; MicroSoft; MR devices; Artifical Intelligence; Disaster Countermeasure; Disaster Recognition; Internet of Things; Mixed-Reality